Governing the sorption and sensing properties of titanium phthalocyanines by means of axial ligands - Sen, Zafer; Tarakci, Deniz Kutlu; Gurol, Ilke; Ahsen, Vefa; Harbeck, Mika (ELSEVIER SCIENCE SA, 2016)
Phthalocyanines are well-established sensing materials for chemical sensors such as quartz crystal microbalance (QCM), surface acoustic wave, or conductive sensors due to their superb sensing qualities and the wide manifold in their sorption properties. The sensing characteristics are determined by the metal ion center and substituents attached to the periphery of the ring system. In this work, a novel method to change the sorption characteristics of phthalocyanines and thereby to govern sensor sensitivity and selectivity is presented by using axial ligands attached to phthalocyanines with a suitable metal ion center. This has been proven to be a simple method to create a library of compounds having very diverging sensing properties using a single base compound. Fourteen axially substituted titanium phthalocyanines were tested using the QCM in their responses to vapors of selected volatile compounds including DMMP. Generally, the axially substituted phthalocyanines have shown excellent sensor characteristics. It was found that the axial ligand has a strong influence on the sensor responses and selectivity for certain analytes was achieved. The use of axial ligands to govern the sensing features of phthalocyanines is considered a promising approach for sensitive material development and advantageous due to the rather simple preparation method. (c) 2016 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Axial substitution; Catechol derivatives; Chemical gas sensor; Quartz crystal microbalance; Volatile organic compounds; DMMP sensing; CHEMICAL SENSORS; SUBSTITUTED PHTHALOCYANINES; SILICON(IV) PHTHALOCYANINES; PHOTODYNAMIC ACTIVITIES; CONDUCTING POLYMERS; THIN-FILMS; FLUOROALKYLOXY; COBALT; ARRAYS; COPPER; Chemistry; Electrochemistry; Instruments & Instrumentation